Adjusting conventional FRAX estimates of fracture probability according to the recency of sentinel fractures - Kanis, John A (Osteoporos Int, 2020)
SUMMARY: The risk of a recurrent fragility fracture is particularly high immediately following the fracture. This study provides adjustments to FRAX based fracture probabilities accounting for the site of a recent fracture. INTRODUCTION: The recency of prior fractures affects subsequent fracture risk. The aim of this study was to quantify the effect of a recent sentinel fracture, by site, on the 10-year probability of fracture determined with FRAX. METHODS: The study used data from the Reykjavik Study fracture register that documented prospectively all fractures at all skeletal sites in a large sample of the population of Iceland. Fracture probabilities were determined after a sentinel fracture (humeral, clinical vertebral, forearm and hip fracture) from the hazards of death and fracture. Fracture probabilities were computed on the one hand for sentinel fractures occurring within the previous two years and on the other hand, probabilities for a prior osteoporotic fracture irrespective of recency. The probability ratios provided adjustments to conventional FRAX estimates of fracture probability for recent sentinel fractures. RESULTS: Probability ratios to adjust 10-year FRAX probabilities of a major osteoporotic fracture for recent sentinel fractures were age dependent, decreasing with age in both men and women. Probability ratios varied according to the site of sentinel fracture with higher ratios for hip and vertebral fracture than for humerus or forearm fracture. Probability ratios to adjust 10-year FRAX probabilities of a hip fracture for recent sentinel fractures were also age dependent, decreasing with age in both men and women with the exception of humerus fractures. CONCLUSION: The probability ratios provide adjustments to conventional FRAX estimates of fracture probability for recent sentinel fractures.